Audit Tingkat Kematangan Proses Internal Key Logistics System Menggunakan Kerangka Kerja Cobit 4.1 Pada Perusahaan Ekspedisi XYZ - Rubhasy, Albaar; Milasari, Dewi Murti (PETIR, 2020)
The purpose of this study is to evaluate the level of IT maturity that occur in XYZ Shipping Company using COBIT 4.1 framework as a best practice in information technology audit. The company is highly depend on Key Logistics System as a core system in shipping process. For this reason, the company wants to focus on internal processes by increasing efficiency while minimizing costs, so COBIT IT Process was chosen: PO3, AI2, AI5, AI3, AI4, AI7, PO6, DS3, DS7, DS8, DS9, PO5, and DS6. An assessment was conducted on 26 Key Logistics System users as respondents. Stages of research to be carried out include: identification of the COBIT 4.1 process; data collection; measurement of current and target maturity levels; gap analysis; and preparation of recommendations. Result has shown that the average maturity score of the Key Logistics System is 3,50 or in maturity level 4 (managed). At this level the key logistics system process has been carried out and part of it has been standardized. However, results shows that there are some gaps below the target, such as IT Process PO5, AI2, and AI5 which have maturity level 3 (defined). In order to improve the maturity level, XYZ Shipping Company has to optimize the IT investement, application maintenance, and IT resources.